Islamic Banks and Corporate Social Responsibility - e.g. Basoad, MB (My University, 2023)
The primary goal of this thesis is to further knowledge of Islamic perspectives on corporate social responsibility (CSR) and commercial financial performance in the context of international banking. CSR is a significant subject in business, particularly in Islamic financing. This study first investigates the connection between CSR initiatives conducted by Islamic banks and conventional financial measures frequently used in Western studies, focusing on the efficiency of cost, revenue, and profit. Published investigations that process and approach the connection between CSR and fiscal efficiency in Islamic banking are few, far between, outdated, or narrow in scope. The study also investigates the relationship between CSR initiatives and socioeconomic accounting metrics, which are more in line with the socioeconomic goals of Islamic banks. Finally, the research discusses the amount and quality of CSR in both standalone CSR reports and yearly reports. The study's results indicated that while Islamic CSR activities at Islamic banks are not given more attention, they have been progressively growing in number and quality or efficacy. Regarding Islamic banks worldwide, there is little evidence supporting the idea that CSR programs are connected to financial and socioeconomic performance. However, the profit-sharing ratio and the Zakat performance ratio provide some evidence that CSR, as evaluated following the Standards, is linked to socioeconomic indices. The survey also discovered that Malaysian Islamic banks prefer to interpret Shariah more liberally to compete due to the multicultural makeup of their clientele.
Keywords: societal responsibility; Islam; social responsibility; corporate responsibility; banking sector; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance